A Content Analysis of Critical Thinking Repesentation in English Textbook for Twelve Grades - Rohmatika Anggraini Putri Hestrian; Sekar Lathifatul Aliyah; Pradita Lina Dewi Afifah (UICELL, 2020)
This paper discovers the representation of critical thinking in an English textbook for twelve grades, which using curriculum 2013. It is a revised edition in 2018 published by the Ministry of Education and Culture in Indonesia. Content analysis and descriptive qualitative were utilized to conduct this paper. Subsequently, the critical thinking framework created by Ilyas was applied to obtain the data. This paper aims to find out about the existence of critical thinking in the textbook to support the increase of critical thinking in students. The paper's findings showed that the textbook contained a few critical thinking elements related to the framework.